Obesity, Inflammation, and Immune System in Osteoarthritis - Nedunchezhiyan, Udhaya; Varughese, Ibin; Sun, Antonia RuJia; Wu, Xiaoxin; Crawford, Ross; Prasadam, Indira (Frontiers in Immunology, 2022)
Obesity remains the most important risk factor for the incidence and progression of osteoarthritis (OA). The leading cause of OA was believed to be overloading the joints due to excess weight which in turn leads to the destruction of articular cartilage. However, recent studies have proved otherwise, various other factors like adipose deposition, insulin resistance, and especially the improper coordination of innate and adaptive immune responses may lead to the initiation and progression of obesity-associated OA. It is becoming increasingly evident that multiple inflammatory cells are recruited into the synovial joint that serves an important role in pathological changes in the synovial joint. Polarization of macrophages and macrophage-produced mediators are extensively studied and linked to the inflammatory and destructive responses in the OA synovium and cartilage. However, the role of other major innate immune cells such as neutrophils, eosinophils, and dendritic cells in the pathogenesis of OA has not been fully evaluated. Although cells of the adaptive immune system contribute to the pathogenesis of obesity-induced OA is still under exploration, a quantity of literature indicates OA synovium has an enriched population of T cells and B cells compared with healthy control. The interplay between a variety of immune cells and other cells that reside in the articular joints may constitute a vicious cycle, leading to pathological changes of the articular joint in obese individuals. This review addresses obesity and the role of all the immune cells that are involved in OA and summarised animal studies and human trials and knowledge gaps between the studies have been highlighted. The review also touches base on the interventions currently in clinical trials, different stages of the testing, and their shortcomings are also discussed to understand the future direction which could help in understanding the multifactorial aspects of OA where inflammation has a significant function.